Anticancer Activities of Chemical Constituents from Leaves and Twigs of Mitrephora winitii - Sukee Sukdee; Puttinan Meepowpan; Narong Nantasaen; Siriporn Jungsuttiwong; Sarinya Hadsadee; Wilart Pompimon (Universitas Gadjah Mada, 2021)
The genus Mitrephora has been investigated and its anti-inflammatory, anti-bacterial and anti-parasitical activities were examined along with its potential as an anti-cancer cell line and inhibitor for platelet aggregation. In this work, air-dried leaves and twigs of M. winitii were grounded and extracted with n-hexane, ethyl acetate and methanol, respectively. Chromatographic separations of these extracts led to the isolation of three known compounds and one new compound (compound 2). The chemical structures of these were identified using spectroscopic investigation of 1D- and 2D-NMR and the resulting data confirmed these as stigmasterol (1), (3,4-dimethoxyphenyl)(5-(3,4-dimethoxyphenyl)-4-(hydroxymethyl)tetrahydrofuran-3-yl)methanol (2), diayangambin (3), and methyl-L-inositol (4). The chemical constituents were reported the first time in M. winitii. Compound 2 showed anti-cancer cell lines with ED50 13.07 µg/mL against KB cells and then was tested for cytotoxicity against MCF-7 cells with ED50 11.77 µg/mL.